Relation between aluminum toxicity and sugarcane (Saccharum spp.) - Sobral, Antônio Fernando de; Guimarães, Vladimir Oliveira da Silva (Pesquisa Agropecuaria Brasileira, 1992)
Results from 14 plant cane liming trials carried out in Pernambuco State, Brazil, were utilized for establishing levels of aluminum toxicity expressed by Al+3 and their saturation "m" (m = Al+3 .100/Al+3 + S). Relative cane yields (Ry = 100.yield without lime/ yield with lime) were correlated with both and in the two cases, the best correlation was obtained by using the equation 1/y = a + bx, with correlation coefficient of 0,88** and 0,92** respectively. The soil aluminum toxicity degress expressed in meq/100 g were established as low (< 0,4); medium (0,4 - 0,8); high (0,8 - 1,2) and very high (> 1,2). Degress of Al+3 saturation (%) were the following ones: low (< 18%); medium (18 - 30); high (30 - 45) and very high (> 45%).
Keywords: soil acidity; liming; sugarcane